Hidradenitis Suppurativa: Case Series at the University of Port Harcourt Teaching Hospital and Literature Review - Gbeneol, T. J.; Onwuagha, I. C. (British Journal of Healthcare and Medical Research, 2025)
Background: Hidradenitis Suppurativa (HS) is highly debilitating for patients, both physically and psychologically. Patients experience recurrent painful abscesses and malodorous discharge necessitating regular dressings. This can lead to social isolation, failed relationships, and depression. Because of the varying clinical manifestations and sites involved in the disease, patients with HS present to, or are referred to many different specialties. Method: In the Plastic and Reconstructive Surgical Unit of the University of Port Harcourt Teaching Hospital, only10 cases were documented in the span of 5 years from 2018 to 2023.Data collected were entered in Microsoft Excel 2010. Analysis was done using Epi-info version 7.0 Charts were produced. Results: There were 10 cases, 4 males and 6 Females. The age range was from 17 to 48 years. Frequency of depilation of axillary hair was the most common etiology, with 60% of them having chronic history of comedones and acne. Conclusion: HS is a complex and debilitating disease, which is still poorly understood. The control of sinuses is probably the key to the condition. No medical treatment resolves sinuses once formed and only radical surgery may succeed in its ability to eradicate sinuses. Early recognition, collaboration between dermatologist and surgeon and good uncompromising surgical principles of enbloc wound excision, cover with fasciocutaneous flaps and complete removal of sinuses is key to effective control.